Kajian Sistem Pengembangan Balai Benih Tanaman Kota Banjarbaru - Mariani Mariani; Djoko Santoso (Universitas Lambung Mangkurat, 2011)
The availability of appropriate production facilities, both on time, right quantity, right quality and right price is a major prerequisite in order to increase productivity. Seed quality is one factor for the weakness of production facilities. The existence of Agricultural Seed Center in certain areas is an effort to get high quality seeds. The purpose of this study is to analyze the capability of Agricultural Seed Center in an effort to produce quality seed, seen from the opportunities, challenges and also strategies to develop Agricultural Seed Center become more advanced. Review of the internal capabilities of Agricultural Seed Center in Banjarbaru covers the physical aspects; aspects of human resources, financial resources and management aspects of Agricultural Seed Center in Banjarbaru. The research of Agricultural Seed Center is anticipatory action in serving the needs of seed food agricultural commodities. But the fundamental weaknesses such as limited water resources, facilities and electrical energy are the bottleneck of this program so it must be revamped thoroughly.